Genotypic variation in rates of photosynthesis and transpiration of Stylosanthes - Tripathi, R.K.; Tiwari, H.S.; Bhatt, R.K.; Sharma, M.S. (Indian Journal of Agroforestry, 2020)
Twenty promising genotypes of Stylosanthes belonging to S. hamata, S. scabra, S. seabrana and S. viscosa were studied for their photosynthesis and transpiration under semi-arid tropics. The rate of photosynthesis in different genotypes ranged from 19.65 µ mole/m2/s to 27.67 µ mole/m2/s. Maximum rate of photosynthesis was recorded in S. scabra cv seca (27.67 µ mole/m2/s) followed by S. seabrana RRR 94-93 (26.12 µ mole/m2/s) and minimum in S. hamata 110135 (19.65 µ mole/m2/s). The transpiration rate ranged from 8.40 m mole/m2/s (S. hamata (Diploid) 61670 to 13.33 m mole/m2/s (S. scabra RRR 94-93). The stomatal conductance ranged from 0.58 to 1.12 (m mol/m2/sec) being maximum in S. scabra 2534 followed by S. scabra cv. seca and minimum in S. hamata 110135 and S. scabra cv q 10042 which was at par to S. hamata diploid (61670). Maximum carboxylation efficiency was recorded in S. scabra cv. seca followed by S. scabra RRR 94-100 and S. seabrana 2534 and minimum in S. hamata 100135. The ratio between rates of photosynthesis and transpiration, which indicate instantaneous water use efficiency, was found to be highest in S. scabra (RRR 94-100) and minimum in S. scabra (93116). All the genotypes accumulated higher chlorophyll a as compared to chl b. The accumulation of chlorophyll a ranged from 0.58 mg/gm fresh weight (S. scabra RRR 94-97) to 1.30 mg/gm (S. seabrana 104710) whereas chlorophyll b ranged from 0.19 mg/gm (S. scabra RRR 94-96) to 0.38 mg/gm fresh weight (S. seabrana 104710). There was large variability among the species while among the genotypes within the species, the variability was very low.